India in the Persian World of Letters Ḳhān-i Ārzū among the Eighteenth-Century Philologists - Dudney, Arthur (Oxford University Press, 2022)
This study traces the development of philology (the analysis of literary language) in the Persian tradition in India, concentrating on its socio-political ramifications. The most influential Indo-Persian philologist of the eighteenth century was Sirāj al-Dīn ʿAlī Ḳhān (d. 1756), whose pen-name was Ārzū. Besides being a respected poet, Ārzū was a rigorous theoretician of language whose intellectual legacy was side-lined by colonialism. His conception of language accounted for literary innovation and historical change in part to theorize the tāzah-goʾī [literally, "fresh-speaking"] movement in Persian literary culture. Although later scholarship has tended to frame this debate in anachronistically nationalist terms (Iranian native speakers versus Indian imitators), the primary sources show that contemporary concerns had less to do with geography than with the question of how to assess innovative "fresh-speaking" poetry, a situation analogous to the Quarrel of the Ancients and the Moderns in early modern Europe. Ārzū used historical reasoning to argue that as a cosmopolitan language Persian could not be the property of one nation or be subject to one narrow kind of interpretation. Ārzū also shaped attitudes about reḳhtah, the Persianized form of vernacular poetry that would later be renamed and reconceptualized as Urdu, helping the vernacular to gain acceptance in elite literary circles in northern India. This study puts to rest the persistent misconception that Indians started writing the vernacular because they were ashamed of their poor grasp of Persian at the twilight of the Mughal Empire.